Penerapan Metode SMART (Simple Multi Attribute Rating Technique) Pada Sistem Pendukung Keputusan Kelayakan Pemberian Kredit Motor Bekas Pada Laris Jaya Motor - Miftha, Adi; Saputra, Suhanda (CV. Shofanah Media Berkah, 2023)
The rapid development of information system sophistication is an aspect that can be utilized to achieve convenience. The convenience of this information system is seen to be increasingly widespread with the use of computers which are indeed very widespread in various lives, one of which is in the field of business or business. At this time there is a transition in the method of granting credit which is done manually, into a decision by utilizing electronic technology, namely the use of a Decision Support System. Laris Jaya Motor has its address in South Tangerang, which is domiciled at Jalan Damai Raya, and has been around since December 5, 2022. Laris Jaya Motor is a company engaged in the automotive trade and offers various financing, one of which is by credit. In the credit granting process, the methods used by credit analysts are still conventional and prone to abuse of authority. Therefore, this research activity was carried out to design and build a web-based application, assess creditworthiness using the SMART method and conduct a search for alternative creditworthiness based on the weight of predetermined criteria. The Simple Multi Attribute Rating Technique (SMART) method is a comprehensive decision-making model that takes into account qualitative and quantitative matters. Calculations in the SMART method are very simple so they do not require complicated mathematical calculations. Transparent The process of analyzing alternatives and criteria in SMART can be seen by the user so that the user can understand how the alternative was selected.